Development Lughotuna Application in Arabic Learning: (Case Study at Madrasah Tsanawiyah Negeri 1 Sidoarjo) - Tri Septianto; Ainaini Ratna Noeri; Dewi Kristanti (Tarbiyah Departement collaboration with AMCA, 2022)
Arabic language learning that is not optimal in class VII B at MTs Negeri 1 Sidoarjo is caused by the learning media used so far that is less attractive, and the teacher needs to include the four skills that the teacher into the learning media must own. So it is necessary to develop a learning media to help optimize learning. This study aims to explain and examine the learning media developed in the form of an android application called Lughotuna. The mixed method was used in this study. Data is sourced from informants who know the focus, such as school principals and learning admins obtained by observation and interviews. The supporting data comes from various books, journals and other encyclopedias. The data were then analyzed quantitatively and qualitatively. Learning media development includes 1) problem identification; 2) product design; 3) validation; and 4) product publication. In product design, there are two validations: media design validation and media content validation. Media design validation uses four aspects of assessment, including 1) ease of use and navigation; 2) aesthetics or beauty; 3) media integration, and 4) technical quality. In validating media content, three aspects of assessment are used, namely 1) suitability; 2) quality and purpose of content; and 3) instructional quality. In validating media design and media content, possible results are obtained.